HUBUNGAN KEKUATAN OTOT LENGAN DENGAN SERVIS ATAS DALAM PERMAINAN BOLA VOLI - Setiawan, Anang; Mulyani, Sri; Kharisma, Yudhi; Oktriani, Seni (YLPK Mahardhika, 2025)
The purpose of this study was to determine the relationship between arm muscle strength and top serve skills in volleyball games. The method used is the correlation method. The population in this study is members of the sports student activity unit of the volley ball division of Universitas Darul Ma’arif Indramayu. The sample used in this study was 10 female members. The technique used in this sampling uses purposive sampling. The data collection technique used is a test. The instruments in this study used push up tests and upper service skill tests. Data analysis techniques use mean tests, standard deviations, normality tests and hypothesis tests. Based on data analysis, the results showed that there was a relationship between arm muscle strength and upper serve skills in volleyball games with a very strong level of relationship.